Algorithm of Differentiated Approach to the Treatment of CHD Patients with Impaired Homocysteine and Vitamin D Metabolism before and after Coronary Artery Bypass Grafting - O. S. Nikonenko; A. O. Nikonenko; K. O. Chmul; V. V. Osaulenko (Ukrainian Journal of Cardiovascular Surgery, 2020)
For many years, cardiovascular diseases have been a major cause of morbidity and mortality worldwide. In modern society these have become one of the most pressing medical and social problems. To date, progression of coronary heart disease (CHD) and its complications is strongly associated with increased homocysteine (HC) level and hypovitaminosis D. However, medical literature does not sufficiently cover the issues of drug treatment of patients with metabolic disorders after coronary artery bypass grafting, therefore, more detailed study of this problem is required.The aim. To develop a differentiated approach to the medical treatment of CHD patients before and after direct myocardial revascularization.Materials and methods. The study analyzed the data of 133 patients, 117 (87.96%) men and 16 (12.03%) women, diagnosed with CHD. In these patients, the levels of homocysteine and vitamin D were evaluated. Depending on the levels of hyperhomocysteinemia and vitamin D, the patients were divided into 3 groups.Results. About 70% of the patients examined had elevated blood homocysteine levels greater than 15 ¤mol/L. Based on selective CAG (MSCT CA) findings and complete examination, myocardial revascularization was indicated in 133 patients, as recommended by the 2018 ESC/EACTS Guidelines on myocardial revascularization. In 95% of cases (126 patients), direct myocardial revascularization was performed. All the patients received standard therapy preoperatively, and after getting results of HC and vitamin D tests, metabolic therapy, including folic acid, vitamins B6, B12 and D, depending on HC and vitamin D levels, was prescribed.Conclusions. Hyperhomocysteinemia and hypovitaminosis D provoke impaired endothelial vasomotor function and activate neointimal hyperplasia. Patients with hyperhomocysteinemia and vitamin D deficiency should receive metabolic therapy based on folic acid, vitamins B 6 and B12, and vitamin D, both preoperatively and postoperatively. The first control of HC and vitamin D levels is carried out within 3 months after the treatment initiation.